2019
DOI: 10.25130/tjas.19.4.8
|View full text |Cite
|
Sign up to set email alerts
|

Urban Growth Mapping Using Remote Sensing and GIS Techniques, case study: Darbandikhan, Kurdistan Region, Iraq

Abstract: Change in land use and land cover, as one of the most important factors of global-scaled environmental transformations, is considered as heart of the sustainable development debate. It is approved that humans are the main driving force that altering the land cover of the globe. In order to attain substantial development, urban authorities should think of useful tools to monitor how the land is now used to apprise future plan. The apprehension of urban change is crucial for making optimal decision and suitable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Whereas, infection fatality rate of the population is intrinsically related to age-specific infection pattern. Therefore, taking public health measures to protect vulnerable age groups can drastically reduce the death rate [33]. It is also revealed that the highest rang of infection was recorded for the age group 60-69 years old, which was 241 cases of total 1152 cases, which could be due to lack of immunity and chronic diseases, while the lowest infections were between age group 10-19 years old because of high level of immunity, which was 8 cases, altogether.…”
Section: Conclusion and Recommendationsmentioning
confidence: 97%
“…Whereas, infection fatality rate of the population is intrinsically related to age-specific infection pattern. Therefore, taking public health measures to protect vulnerable age groups can drastically reduce the death rate [33]. It is also revealed that the highest rang of infection was recorded for the age group 60-69 years old, which was 241 cases of total 1152 cases, which could be due to lack of immunity and chronic diseases, while the lowest infections were between age group 10-19 years old because of high level of immunity, which was 8 cases, altogether.…”
Section: Conclusion and Recommendationsmentioning
confidence: 97%
“…The research area is located in northern Iraq, Kurdistan region, Duhok province, between latitudes 37°00′00′′ N and 37°07′30′′ N and longitudes 42°27′30′′ E and 42°47′30′′ E [12], and 585 m above the sea level [13]. It has a population of over 340,900 (2018).…”
Section: Study Areamentioning
confidence: 99%
“…Spatial variability of soil characteristics is affected by topographical features, land use type, soil depth, soil formation factors and processes, human activity and time [15][16][17] . RS and GIS are used in many areas related to the nature of the earth, the environment and the exploitation of lands in agricultural areas and urban growth [18,19] , as well as the exploitation of the natural environment in the fields of tourism, which is a basic pillar of the country's economy [20] . This technique is also used in monitoring the occurrence of natural disasters such as forest fires, their area and how they are distributed to minimize the damage [21,22] .…”
Section: Introductionmentioning
confidence: 99%